Choosing Higher Education for Senior High School and Upper Education Students - Martínez-Martínez, Asunción (2016)
Choosing a university degree for next year is a topic of interest for educational levels of higher education, since they allow to decide what kind of students access the different university degrees; also among the factors that affect concisely are qualifications or personal profile, therefore we propose the following study with the objective to determine the most popular degrees with limitation, as without it, of senior high school and upper education students of Granada, as well as describe the academic and socio-demographic characteristics, and evaluate the influence academic qualifications, branch of studies and gender have in choosing college degree. A total of 1,164 students in last year of high school and upper education students participated, which allowed the recording and evaluation of the variables mentioned above. Results showed that medicine, teaching and engineering degrees are the most in demand without any kind of limitation, while with limitation it changes medicine for nursing, also senior students from Granada had a remarkable average note, males opt more for upper education training and show worse grades and women choose bachelor with slightly higher average grades, verifying the influence academic qualifications, branch of studies and gender have in choosing a degree with or without limitation. Thus, due to its more altruistic nature, female students postulate in health science and social degrees, with higher grades, while male students prefer more technical qualifications with worse grades.